2011
DOI: 10.1007/s11409-010-9066-0
|View full text |Cite
|
Sign up to set email alerts
|

Consistent results with the consistency hypothesis? The effects of epistemic beliefs on metacognitive processing

Abstract: We explored relations between students' epistemic beliefs, metacognitive monitoring and recall performance in the context of learning physics through metaphor. Eighty-three university undergraduate students completed questionnaires designed to measure their epistemic beliefs and prior knowledge about Newtonian physics. Students were epistemically profiled as rational, empirical, or metaphorical in their approaches to knowing. Using a think-aloud protocol, students read a text on Newton's First and Third Laws. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…study epistemic perspective and epistemic processing. The studies described in section 1.2.2., among others (e.g., Lin, Liang, & Tsai, 2012;Muis & Franco, 2010;Muis, Kendeou, & Franco, 2011;Stahl, Pieschl, & Bromme, 2006), suffer from the same limitations as studies that explored relations between epistemic perspective and learning: They employed self-report measures to assess epistemic processing, which have notable psychometric problems (see Winne, Jamieson-Noel, & Muis, 2002). Furthermore, research examining relations between epistemic perspective and epistemic processing examined epistemic processing after engagement in an activity, employing offline methods through retrospective interviews (e.g., Mason, et al, 2010) or questionnaires in which participants reported the frequency of engagement in epistemic processing in a particular course (Muis & Franco, 2010).…”
Section: Reflection On the Methodological Approaches Employed In Prevmentioning
confidence: 99%
“…study epistemic perspective and epistemic processing. The studies described in section 1.2.2., among others (e.g., Lin, Liang, & Tsai, 2012;Muis & Franco, 2010;Muis, Kendeou, & Franco, 2011;Stahl, Pieschl, & Bromme, 2006), suffer from the same limitations as studies that explored relations between epistemic perspective and learning: They employed self-report measures to assess epistemic processing, which have notable psychometric problems (see Winne, Jamieson-Noel, & Muis, 2002). Furthermore, research examining relations between epistemic perspective and epistemic processing examined epistemic processing after engagement in an activity, employing offline methods through retrospective interviews (e.g., Mason, et al, 2010) or questionnaires in which participants reported the frequency of engagement in epistemic processing in a particular course (Muis & Franco, 2010).…”
Section: Reflection On the Methodological Approaches Employed In Prevmentioning
confidence: 99%
“…and actual epistemological realities of engineering that our research seeks to investigate. Finally, much of the research using developmental models has failed to take into account the increasingly supported domain-specific nature of personal epistemology (Hofer, 2000;Muis et al, 2006;Muis, Kendeou, & Franco, 2011). A young college student's apparently general absolutism could adapt quite well to the traditional, lecture-based courses experienced by many engineering students.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly, researchers are approaching personal epistemology as domain-specific, arguing the attempt to describe an individual's generalized personal epistemology is misguided and explains the poor validity of quantitative measures (Greene, Torney-Purta, & Azevedo, 2010;Lim on Luque, 2003;Muis et al, 2006). The most successful quantitative assessments of personal epistemology limit their measurements to a single academic domain like physics or mathematics (Franco et al, 2011;Greene, Torney-Purta, & Azevedo, 2010). These researchers call for the development of domain-specific models of personal epistemology.…”
Section: Psychological Studiesmentioning
confidence: 99%
See 2 more Smart Citations